GMAT Question of the Day: Daily via email | Daily via Instagram New to GMAT Club? Watch this Video

It is currently 06 Apr 2020, 10:45

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Close

Request Expert Reply

Confirm Cancel

If (Z-3)^2 = 12,then 2z(z-6)=

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
TAGS:

Hide Tags

Find Similar Topics 
GMAT Club team member
User avatar
V
Status: GMAT Club Team Member
Affiliations: GMAT Club
Joined: 02 Nov 2016
Posts: 5387
GPA: 3.62
If (Z-3)^2 = 12,then 2z(z-6)=  [#permalink]

Show Tags

New post 05 Feb 2020, 07:15
00:00
A
B
C
D
E

Difficulty:

  25% (medium)

Question Stats:

79% (02:07) correct 21% (02:16) wrong based on 39 sessions

HideShow timer Statistics

If \((Z-3)^2 = 12\),then \(2z(z-6)=\)

A. 6

B. 9

C. 10

D. 15

E. 27

_________________
Director
Director
avatar
G
Joined: 14 Dec 2019
Posts: 506
Location: Poland
GMAT 1: 570 Q41 V27
WE: Engineering (Consumer Electronics)
Premium Member CAT Tests
Re: If (Z-3)^2 = 12,then 2z(z-6)=  [#permalink]

Show Tags

New post 05 Feb 2020, 07:22
1
If \((Z−3)^2=12\), then \(2z(z−6)=\)?

A. 6

B. 9

C. 10

D. 15

E. 27

\((Z−3)^2=12\) -> \(Z^2 -6Z + 9 = 12\) -> \(Z^2 = 6Z + 3 \) -> \(2z^2 - 12Z = 12Z + 6 -12Z = 6\)

Answer - A
Target Test Prep Representative
User avatar
V
Status: Founder & CEO
Affiliations: Target Test Prep
Joined: 14 Oct 2015
Posts: 9972
Location: United States (CA)
Re: If (Z-3)^2 = 12,then 2z(z-6)=  [#permalink]

Show Tags

New post 09 Feb 2020, 04:20
SajjadAhmad wrote:
If \((Z-3)^2 = 12\),then \(2z(z-6)=\)

A. 6

B. 9

C. 10

D. 15

E. 27


Foiling the given equation, we have:

Z^2 - 6Z + 9 = 12

Z^2 - 6Z - 3 = 0

Z^2 - 6Z = 3

Z(Z - 6) = 3

So 2 * Z(Z - 6) = 2 * 3 = 6.

Answer: A
_________________

Scott Woodbury-Stewart

Founder and CEO

Scott@TargetTestPrep.com
TTP - Target Test Prep Logo
197 Reviews

5-star rated online GMAT quant
self study course

See why Target Test Prep is the top rated GMAT quant course on GMAT Club. Read Our Reviews

If you find one of my posts helpful, please take a moment to click on the "Kudos" button.

GMAT Club Bot
Re: If (Z-3)^2 = 12,then 2z(z-6)=   [#permalink] 09 Feb 2020, 04:20
Display posts from previous: Sort by

If (Z-3)^2 = 12,then 2z(z-6)=

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  





Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne